The 5 Untranslated Region of the Human T-Cell Lymphotropic Virus Type 1 Mrna Enables Cap-Independent Translation Initiation - Garcia Huidobro-Toro, J (American Society for Microbiology, 2014)
The human T-cell leukemia virus type 1 (HTLV-1) is a complex human retrovirus that causes adult T cell leukemia and of HTLVassociated myelopathy/tropical spastic paraparesis. The mRNA of some complex retroviruses, including the human and simian immunodeficiency viruses (HIV and SIV), can initiate translation using a canonical cap-dependent mechanism or through an internal ribosome entry site (IRES). In this study, we present strong evidence showing that like HIV-1 and SIV, the 5 -untranslated region (5 UTR) of the HTLV-1 full-length mRNA harbors an IRES. Cap-independent translational activity was evaluated and demonstrated using dual luciferase bicistronic mRNAs in rabbit reticulocyte lysate, in mammalian cell culture, and in Xenopus laevis oocytes. Characterization of the HTLV-1 IRES shows that its activity is dependent on the ribosomal protein S25 (RPS25) and that its function is highly sensitive to the drug edeine. Together, these findings suggest that the 5 UTR of the HTLV-1 full-length mRNA enables internal recruitment of the eukaryotic translation initiation complex. However, the recognition of the initiation codon requires ribosome scanning. These results suggest that, after internal recruitment by the HTLV-1 IRES, a scanning step takes place for the 40S ribosomal subunit to be positioned at the translation initiation codon. © 2014, American Society for Microbiology.